Evaluation of Kapita Selekta College of Islamic Education and its Impact on Student Solution Competence - Muhayat, Imam (Tahta Media Group, 2024)
STAI Denpasar Bali was established in 2008. STAI Denpasar Bali emphasises the offline lecture process even though it is an independent campus. Only if it is not possible to do it offline can it be done online. Lectures in the Islamic Education course aside (KSPI) from theoretically applying practical lectures. The learning objectives are to improve the quality of being skilled at dealing with educational problems and being able to decipher solutions faced by educational institutions. Lecture strategy is a top priority. Starting from lesson planning, learning implementation, and the evaluation stage. In this study, the focus on evaluative strategies has an impact on students' solutive competence in solving problems, being able to implement theory, and being able to carry out new innovations. The evaluative strategy is meant here as a careful plan of activities to achieve specific goals. Meanwhile, solution competence is skilled at solving problems and finding solutions. This research uses an explanatory research method. These include the following value interval categories: 1. Very poor; 2. Less; 3. Enough; 4. Good; and 5. Very good. The indicator is very lacking. The design presented is irregular and does not solve the problem. On the other hand, the indicators are very good, the design is presented systematically, solves problems, can be implemented and is innovative. An analysis of the carrying capacity of activities serves as the foundation for all of this. The results of the study found that the evaluative strategy of the Islamic Education course (KSPI) had an impact on students' solutive competence and obtaining good grades.